Association of Febuxostat to Cardiovascular Mortality in Gout: A Systematic Review - Satria Dharma Setiawan; Dina Anggraini (International Medical Journal Corp. Ltd, 2025)
Introduction: Gout, a systemic metabolic disorder characterized by hyperuricemia, is an independent risk factor for cardiovascular (CV) disease. Febuxostat, a potent xanthine oxidase inhibitor, has demonstrated superior urate-lowering efficacy compared to allopurinol. However, its CV safety profile has been the subject of significant controversy following conflicting results from two major randomized controlled trials (RCTs), the CARES and FAST trials, and a subsequent FDA black box warning regarding increased mortality risk. This systematic review aims to synthesize the current evidence on the association between febuxostat and CV mortality in patients with gout. Methods: A systematic search was conducted in PubMed/MEDLINE, EMBASE, and the Cochrane Central Register of Controlled Trials for RCTs and observational cohort studies comparing the CV safety of febuxostat with allopurinol or other controls in patients with gout or hyperuricemia. Data on primary outcomes (CV mortality, all-cause mortality) and numerous secondary CV outcomes were extracted. The quality of RCTs was assessed using the Cochrane Risk of Bias 2 (RoB 2) tool, and observational studies were assessed with the Newcastle-Ottawa Scale. Results: Seventeen studies, including five major RCTs and twelve observational studies and meta-analyses, were included. A significant signal for increased mortality was identified. The pivotal CARES trial, involving 6,190 high-risk CV patients, found that febuxostat was associated with a statistically significant increase in CV mortality (Hazard Ratio 1.34, 95% Confidence Interval [CI] 1.03–1.73) and all-cause mortality (HR 1.22, 95% CI 1.01–1.47) compared to allopurinol. This finding was supported by a meta-analysis by Cuenca et al. (2019) (Relative Risk for CV death 1.29, 95% CI 1.01–1.66) and an Austrian cohort study. However, a substantial body of conflicting evidence exists. The FAST trial (n=6,128) found febuxostat to be non-inferior to allopurinol, with no increased risk of CV or all-cause mortality. Multiple large-scale cohort studies and meta-analyses corroborated the findings of the FAST trial, reporting no significant difference in mortality or major adverse cardiovascular events (MACE). Discussion: The discrepancy in findings is largely attributable to critical differences in study populations and methodologies between the CARES and FAST trials. CARES enrolled patients with established, severe CV disease who were often initiating urate-lowering therapy, whereas FAST studied a lower-risk population already stable on allopurinol. The high rate of participant discontinuation in the CARES trial represents a significant risk of bias. Emerging evidence suggests the increased risk may be concentrated in the treatment initiation phase or may be linked to sUA fluctuations following treatment discontinuation, rather than a direct pharmacological effect of the drug itself. Conclusion: A significant association between febuxostat and increased cardiovascular mortality has been demonstrated, primarily driven by the CARES trial in a specific high-risk population. While this signal warrants significant clinical caution, it is contradicted by other high-quality evidence. The risk appears conditional rather than universal. Clinical decisions should involve careful patient selection and shared decision-making, reserving febuxostat for patients intolerant to allopurinol, particularly those with a high CV burden.